1980
DOI: 10.1002/art.1780231112
|View full text |Cite
|
Sign up to set email alerts
|

‘Navajo Arthritis’ reconsidered

Abstract: "Navajo arthritis" was described in 1971 as an acute, self-limited, asymmetric polyarthritis of unknown etiology seen in Navajo Indian patients. This description was before published accounts relating HLA-B27 to certain seronegative arthropathies. Review of 92 cases of arthritis seen between 1977 through 1979 in adult Navajo Indians revealed 16 cases of complete Reiter's syndrome, 6 cases of incomplete Reiter's syndrome, and 7 cases of ankylosing spondylitis. The phenotype frequency of HLA-B27 in this Navajo p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Thirteen studies characterizing spondyloarthropathies in Indigenous populations were identified; one of these was on ankylosing spondylitis in three First Nations populations in Canada (Bella Bella, Bella Coola and Haida) and an American Indian population (Pima) in the USA [62], one was from a Canadian Inuit population with spondyloarthritis [20], two from Canadian First Nations populations with ankylosing spondylitis (Haida) [63] and spondyloarthritis (Nuu-Chah-Nulth) [42], two were from the Navajo population with ankylosing spondylitis and reactive arthritis in the USA [64, 65], and seven included analyses on a cohort of Alaskan Native patients with conditions including ankylosing spondylitis, reactive arthritis, psoriatic arthritis and undifferentiated spondyloarthritis [38, 6671]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen studies characterizing spondyloarthropathies in Indigenous populations were identified; one of these was on ankylosing spondylitis in three First Nations populations in Canada (Bella Bella, Bella Coola and Haida) and an American Indian population (Pima) in the USA [62], one was from a Canadian Inuit population with spondyloarthritis [20], two from Canadian First Nations populations with ankylosing spondylitis (Haida) [63] and spondyloarthritis (Nuu-Chah-Nulth) [42], two were from the Navajo population with ankylosing spondylitis and reactive arthritis in the USA [64, 65], and seven included analyses on a cohort of Alaskan Native patients with conditions including ankylosing spondylitis, reactive arthritis, psoriatic arthritis and undifferentiated spondyloarthritis [38, 6671]. …”
Section: Resultsmentioning
confidence: 99%
“…In the Navajo population, 80% of ankylosing spondylitis patients were HLA-B27 positive and 43% had knee involvement [64]. Seventy two percent with reactive arthritis had the characteristic triad of arthritis, conjunctivitis and urethritis, 88% were HLA-B27 positive, 53% had radiographic sacroiliitis, and 33% had uveitis or iritis [65].…”
Section: Resultsmentioning
confidence: 99%